Case Study: Effect of Slow Stroke Back Massage on Pain in Post Sectio Caesarea Mothers - Emilia, Silfi; Kartikasari, Aprilia (Universitas Padjadjaran, 2024)
Pain is an unpleasant experience that can be experienced by post sectio caesarea mothers. 88.2% of post sectio caesarea mothers feel pain. Pain is caused by an incision in the abdomen. Postoperative pain management can be done pharmacologically and non-pharmacologically. Slow stroke back massage can be used as an alternative to pain management with a non-pharmacological approach. This study aims to determine the effect of giving slow stroke back massage therapy on post sectio caesarea pain intensity. The research method used was descriptive case study using numeric rating scale (NRS) instrument. The research subjects were 4 respondents with the criteria of second day post sectio caesarea patients with moderate to severe pain intensity. Respondents were divided into intervention and control groups. The study was conducted for one day with a duration of 20 minutes of therapy for each respondent. The results of the case study showed that respondents had an average pain scale of 5. There was a decrease in the pain scale of post sectio caesarea mothers in the intervention group with an average decrease of 2.5 scales. This decrease occurs due to the mechanism of releasing endorphins which play a role in reducing pain perception in the parasympathetic nervous system. The slow stroke back massage intervention has an effect on reducing the pain scale of post sectio caesarea mothers so that it can be applied in the process of providing nursing care in the clinic.